Establishment of a saliva donor selection for in vitro biofilm growth - Mendes, Thalita [UNESP]; Sales, Luciana Solera [UNESP]; Danelon, Marcelle [UNESP]; Brighenti, Fernanda Lourenção [UNESP] (FapUNIFESP (SciELO), 2023)
Introduction: The utilization of polymicrobial biofilms, with saliva as an inoculum, represents a promising model for in vitro studies on cariogenic biofilms. However, there is still no standardization for selecting saliva donors. Objective: The aim of this study is to establish a methodology for the selection of saliva donors using microbial salivary factors and in vitro biofilm characteristics. Material and method: For saliva donation, twenty volunteers were selected. Volunteers remained 24 h without brushing their teeth and fasted for 2 h before saliva collection. The following parameters were evaluated: total anaerobic bacteria and mutans streptococci viability; minimum inhibitory concentration (MIC) and minimum bactericide concentration (MBC) of chlorhexidine; biofilm forming capacity by biomass assessment; and the susceptibility of biofilms to chlorhexidine. Result: Saliva bacterial viability, biofilm forming capacity and biofilm susceptibility to chlorhexidine were presented as mean and confidence interval (95%). The difference between biofilm (mutans streptococci and Total bacteria) viability after treatment with NaCl 0.9% and 0.2% chlorhexidine diacetate was compared using the Student t-test with a significance level established at 5%. Total anaerobic bacteria viability (median) was 7.28 log 1+CFU/mL (colony forming units/ mL). Mutans streptococci viability in the saliva showed a median of 5.47 log 1+CFU/mL. Biofilm forming capacity showed that biomass had a median of 0.1172 A570. Conclusion: Treatment with chlorhexidine significantly reduced mutans streptococci and total bacteria viability. The methodology for the selection of the saliva donor was successfully established.
Seleção de doadores de saliva para crescimento de biofilme in vitro
Keywords: Biofilm; biomass; chlorhexidine; microbial viability; saliva donor